2011
DOI: 10.1007/s11244-011-9739-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Diffusion-Controlled Hydrocarbon Selectivities in the Fischer–Tropsch Synthesis Over Cobalt Supported on Ordered Mesoporous Silica

Abstract: A series of four cobalt-based catalysts (two of which promoted with ruthenium) supported on SiO 2 or SBA-15 were prepared and tested in the Fischer-Tropsch synthesis at industrially relevant process conditions (483 K, 20 bar, H 2 /CO ratio = 2.1, pellet size: 53-90 lm). The catalysts were characterized by N 2 -adsorption, X-ray diffraction (XRD), temperature-programmed reduction (TPR), H 2 -chemisorption and transmission electron microscopy (TEM). Ru as promoter enhanced the activity but not the selectivity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…This high catalyst dilution, together with an aluminum jacket placed between the reactor and the oven, allowed for an even temperature profile (210 ± 2 °C) along the catalyst bed. A catalyst particle size in the range of 53-90 μm was used in order to suppress the influence of mass transfer on the catalyst performance [3,8,39,40]. The samples were in situ reduced at 350 °C (heating rate =1 °C/min) for 16 h in pure H 2 flow [gas hourly space velocity =7.5 NL/(h·g catalyst )].…”
Section: Catalytic Testingmentioning
confidence: 99%
“…This high catalyst dilution, together with an aluminum jacket placed between the reactor and the oven, allowed for an even temperature profile (210 ± 2 °C) along the catalyst bed. A catalyst particle size in the range of 53-90 μm was used in order to suppress the influence of mass transfer on the catalyst performance [3,8,39,40]. The samples were in situ reduced at 350 °C (heating rate =1 °C/min) for 16 h in pure H 2 flow [gas hourly space velocity =7.5 NL/(h·g catalyst )].…”
Section: Catalytic Testingmentioning
confidence: 99%
“…The use of ordered silica mesostructures as carriers has been instrumental to reveal the impact of pore size [104], morphology [105], and connectivity [101,106] on the stability of the supported metal nanoparticles against agglomeration and growth. Analogous studies revealed the influence of the pore dimension on diffusion phenomena during catalyst operation [107,108]. In recent years, high-resolution spectroscopic methods have reached the spatiotemporal resolution required to detect single turnover events, at the nanoscale, during the catalytic action of porous catalysts [84,109].…”
Section: Recent Examples For the Use Of 3d Model Systems To Guide Catmentioning
confidence: 99%
“…For industry to selectively synthesize a specific type of product is still one of the most important challenges in FTS. 25 Many efforts have been dedicated to investigate the combination of acid catalysts with a conventional FTS catalyst to form a bifunctional catalyst system, in order to increase the product selectivity to a specific range 3-6 . In traditional system, hydrocracking catalysts (acidic zeolites) are usually packed in a 30 separate reactor downstream or a separate layer below the FTS catalyst 7 .…”
Section: Introductionmentioning
confidence: 99%